Productivity evaluation of Eucalyptus urophylla plantation established in dryland ecosystems, East Nusa Tenggara - Sadono, Ronggo; Wardhana, Wahyu; Wirabuana, Pandu Yudha Adi Putra; Idris, Fahmi (Journal of Degraded and Mining Lands Management, 2020)
The establishment of the Eucalyptus urophylla plantation has a potential contribution to the improvement of dryland ecosystem productivity in East Nusa Tenggara. However, the productivity of E. urophylla stand in this area is rarely documented even though it has been managed for more than 20 years. This study was directed to evaluate the growth performance, biomass accumulation, and carbon storage in E. urophylla plantation managed by Timor Tengah Selatan Forest Management Unit (FMU). Data were collected by a field survey using N-trees sampling method. Results demonstrated the mean tree density of E. urophylla in this area was 182 trees/ha with an average stand volume of 150.12 m3/ha. The mean annual increment in volume varied from 1.83 to 19.45 m3/year. The mean biomass accumulation and carbon storage in E. urophylla plantation approached 171.76 and 52.25 Mg/ha. Around 65% of total biomass and carbon storage were accumulated in the stem. Interestingly, the relative contribution of the stem to total biomass increased slowly with diameter class increasing while the dissimilar trend was observed in root, branch, and foliage. Based on the results, this study confirmed that the existence of E. urophylla plantation could increase the productivity of dryland ecosystem in East Nusa Tenggara.